2018
DOI: 10.4028/www.scientific.net/kem.774.161
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tensile Properties and Damage of Continuous Fibre Reinforced 3D-Printed Parts

Abstract: Three-dimensional (3D) printing technology has been traditionally used for the production of prototypes. Recently, developments in 3D printing using Fused Deposition Modelling (FDM) and reinforcement with continuous fibres (fiberglass and carbon fibre), have allowed the manufacture of functional prototypes, considerably improving the mechanical performance of the composite parts. In this work, we characterise the elastic tensile properties of fibre reinforced specimens, considering the variation of several par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 20 publications
1
12
0
4
Order By: Relevance
“…According to their results, the Young's modulus provided by the 10% triangular pattern is higher than that of the 70% rectangular pattern, while the reported tensile strength at yield was almost similar for both infill densities. This confirms the results of Gonzalez-Estrada et al [21], the explanation being that the triangular pattern has more strands oriented in the direction of loading (0 • ) than the rectangular pattern. Another interesting conclusion was that the infill density is not largely influencing the tensile properties (also considering the small dimensions of specimens), while significantly affecting the printing time and cost.…”
Section: Infill Pattern and Densitysupporting
confidence: 91%
See 1 more Smart Citation
“…According to their results, the Young's modulus provided by the 10% triangular pattern is higher than that of the 70% rectangular pattern, while the reported tensile strength at yield was almost similar for both infill densities. This confirms the results of Gonzalez-Estrada et al [21], the explanation being that the triangular pattern has more strands oriented in the direction of loading (0 • ) than the rectangular pattern. Another interesting conclusion was that the infill density is not largely influencing the tensile properties (also considering the small dimensions of specimens), while significantly affecting the printing time and cost.…”
Section: Infill Pattern and Densitysupporting
confidence: 91%
“…Several studies have been dedicated to determine the relation between the infill pattern, density and the mechanical properties of the 3DP specimens. Gonzalez-Estrada et al [21] studied the influence of different infill pattern of Nylon matrix (triangular, rectangular and hexagonal) at two infill densities (20% and 50%) on the tensile strength. The testing results showed that the triangular pattern performed the best and also that the increase of the infill density from 20% to 50% produces only a 3.3% increase in the Young's modulus and 5.5% in the tensile strength.…”
Section: Infill Pattern and Densitymentioning
confidence: 99%
“…These strength values of CGFR composites were reported for fibers parallel to the applied tensile stress. Multiple studies have demonstrated a decrease in mechanical performance as the off-axis fiber angle is increased (Mallick, 1986; Cai et al , 2017; González-Estrada et al , 2018). One study investigated the effects of 0 ∘ , 45 ∘ and 90 ∘ fiber orientation on the E and TS of CGFR-nylon, tests were performed according to ASTM D638 with Type IV specimens–width of 6 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Estrada et al [94] compared carbon reinforced and glass-reinforced continuous fiber composites FFF build parts. The experimental analysis showed that the elastic modulus and ultimate tensile strength of carbon composite parts are superior to glass composite parts.…”
Section: Continuous Fiber Compositesmentioning
confidence: 99%